2022
DOI: 10.1155/2022/8658999
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Meconium Peritonitis: A Clinical Study of Nine Cases

Abstract: Objective. To explore the prenatal ultrasonographic characteristics and pregnancy outcomes of fetal meconium peritonitis (FMP). Methods. Nine patients diagnosed with FMP by routine prenatal examination between January 2015 and December 2020 were identified. Both prenatal ultrasonographic characteristics and pregnancy outcomes associated with these patients were retrospectively analyzed. Results. The mean gestational age at the time of FMP diagnosis was 31.3 ± 4.8 weeks, and the mean gestational age of delivery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The most common ultrasonographic findings include bowel dilatation, intraabdominal calcification, ascites, intraperitoneal pseudocyst, and polyhydramnios. 5,6,10,[14][15][16] Our case is quite unusual because of its unusual course starting from ascites and hyperechoic bowel, presenting further with intraperitoneal pseudocyst with intestinal connection, intraperitoneal calcifications, dilated aperistaltic bowel loops, and polyhydramnion. Pseudocyst was not seen later; a possible explanation is the formation of intestinal fistula.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The most common ultrasonographic findings include bowel dilatation, intraabdominal calcification, ascites, intraperitoneal pseudocyst, and polyhydramnios. 5,6,10,[14][15][16] Our case is quite unusual because of its unusual course starting from ascites and hyperechoic bowel, presenting further with intraperitoneal pseudocyst with intestinal connection, intraperitoneal calcifications, dilated aperistaltic bowel loops, and polyhydramnion. Pseudocyst was not seen later; a possible explanation is the formation of intestinal fistula.…”
Section: Discussionmentioning
confidence: 85%
“…The most common ultrasonographic findings include bowel dilatation, intraabdominal calcification, ascites, intraperitoneal pseudocyst, and polyhydramnios. 5 6 10 14 15 16…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al reported two similar cases where antenatal monitoring of dimensions and observations of distension and ileus led to suspicion of meconium peritonitis [ 1 ]. Antenatal diagnosis of meconium peritonitis is now possible with improved imaging techniques such as prenatal graded compression ultrasound, which is highly accurate, aiding in early diagnosis and providing crucial information; however, its sensitivity varies and relies heavily on the operator's skill [ 7 ]. Abdominal X-rays in various positions (supine, upright, and lateral) are usually insufficient for identifying intraperitoneal free gas.…”
Section: Discussionmentioning
confidence: 99%
“…During post-natal diagnosis, occasionally, an abdominal roentgenogram reveals large egg-shell calcification in the case of a long-standing meconium pseudocyst. In Fu et al [ 8 ], the average gestational age for diagnosis of fetal meconium peritonitis was found to be 31.3 ± 4.8 weeks, and the ultrasound revealed intestinal dilation (most common), intraperitoneal calcification, fetal ascites, and intraperitoneal pseudocysts, and polyhydramnios. Some studies claimed that fetal MRI has better diagnostic accuracy between 51% and 73.4% for a fetus with an abdominal cystic lesion and, thus, aids in counseling and planning delivery setting.…”
Section: Discussionmentioning
confidence: 99%